Comparison of Effectiveness between Abdominal Vibration Stimulation and Walking Exercise for Bowel Cleansing before Therapeutic Colonoscopy - Noh, Choong-Kyun; Kim, In Sung; Lee, Gil Ho; Park, Jin Woong; Lee, Eunyoung; Park, Bumhee; Hong, Hye Jeon; Lim, Sun Gyo; Shin, Sung Jae; Kim, Jin Hong; Lee, Kee Myung (Gut and liver, 2020)
Adequate bowel preparation is important for successful colonoscopy. We aimed to evaluate the clinical feasibility and effectiveness of abdominal vibration stimulation in bowel preparation before therapeutic colonoscopy.Background/AimsAdequate bowel preparation is important for successful colonoscopy. We aimed to evaluate the clinical feasibility and effectiveness of abdominal vibration stimulation in bowel preparation before therapeutic colonoscopy.A single center, prospective, randomized, investigator-blinded study was performed between January 2016 and December 2016. Patients for therapeutic colonoscopy were prospectively enrolled and assigned to either the vibrator group or walking group. Patients who refused to participate in this study as part of the experimental group consented to register in the control group instead. During the preparation period, patients assigned to the walking group walked ≥3,000 steps, whereas those assigned to the vibrator group received abdominal vibrator stimulation and restricted walking. All patients received the same colon cleansing regimen: 4-L split-dose polyethylene glycol (PEG) solution.MethodsA single center, prospective, randomized, investigator-blinded study was performed between January 2016 and December 2016. Patients for therapeutic colonoscopy were prospectively enrolled and assigned to either the vibrator group or walking group. Patients who refused to participate in this study as part of the experimental group consented to register in the control group instead. During the preparation period, patients assigned to the walking group walked ≥3,000 steps, whereas those assigned to the vibrator group received abdominal vibrator stimulation and restricted walking. All patients received the same colon cleansing regimen: 4-L split-dose polyethylene glycol (PEG) solution.Three hundred patients who received PEG solution for therapeutic colonoscopy were finally enrolled in this study (n=100 per group). Bowel cleansing with abdominal vibration stimulation showed almost similar results to that with walking exercise (Boston Bowel Preparation Scale score for the entire colon: vibrator vs walking vs control, 7.38±1.55 vs 7.39±1.55 vs 6.17±1.15, p<0.001). There were no significant differences between the vibrator group and walking group regarding instances of diarrhea after taking PEG, time to first diarrhea after taking PEG, total procedure time, and patient satisfaction.ResultsThree hundred patients who received PEG solution for therapeutic colonoscopy were finally enrolled in this study (n=100 per group). Bowel cleansing with abdominal vibration stimulation showed almost similar results to that with walking exercise (Boston Bowel Preparation Scale score for the entire colon: vibrator vs walking vs control, 7.38±1.55 vs 7.39±1.55 vs 6.17±1.15, p<0.001). There were no significant differences between the vibrator group and walking group regarding instances of diarrhea after taking PEG, time to first diarrhea after taking PEG, total procedure time, and patient satisfaction.This study indicates that, compared with conventional walking exercise, abdominal vibration stimulation achieved similar rates of bowel cleansing adequacy and colonoscopy success without compromising safety or patient satisfaction.ConclusionsThis study indicates that, compared with conventional walking exercise, abdominal vibration stimulation achieved similar rates of bowel cleansing adequacy and colonoscopy success without compromising safety or patient satisfaction.